Nipple sparing versus skin sparing mastectomy: a systematic review protocol. Issue 5 (20th May 2016) - Agha, Riaz A; Wellstead, Georgina; Sagoo, Harkiran; Al Omran, Yasser; Barai, Ishani; Rajmohan, Shivanchan; Fowler, Alexander J; Orgill, Dennis P; Rusby, Jennifer E
Abstract : Introduction: Breast cancer has a lifetime incidence of one in eight women. Over the past three decades there has been a move towards breast conservation and a focus on aesthetic outcomes while maintaining oncological safety. For some patients, mastectomy is the preferred option. There is growing interest in the potential use of nipple sparing mastectomy (NSM). However, oncological safety remains unproven, and the benefits and indications have not been clearly identified. The objective of this systematic review will be to determine the safety and efficacy of NSM as compared with skin sparing mastectomy (SSM). Methods and analysis: All original comparative studies including; randomised controlled trials, cohort studies and case–control studies involving women undergoing either NSM or SSM for breast cancer will be included. Outcomes are primary—relating to oncological outcomes and secondary—relating to clinical, aesthetic, patient reported and quality of life outcomes. A comprehensive electronic literature search, designed by a search specialist, will be undertaken. Grey literature searches will also be conducted. Eligibility assessment will occur in two stages; title and abstract screening and then full text assessment. Each step will be conducted by two trained teams acting independently. Data will then be extracted and stored in a database with standardised extraction fields to facilitate easy and consistent data entry. Data analysis will be undertaken to explore the relationship between NSM or SSM and preselected outcomes, heterogeneity will be assessed using the Cochrane tests. Ethics and dissemination: This systematic review requires no ethical approval. It will be published in a peer-reviewed journal. It will also be presented at national and international conferences. Updates of the review will be conducted to inform and guide healthcare practice and policy.